(3HOGFY GdHQgGf Ydi YeOI GdYQaGfs - (3eUWai Hf YHO GdQMef Hf eMeO GdCRejQi, (B1156 (3g` s; (3NjQ Gddg Hf NjQ GdOjf GdbGQj GdNWjHs
(3ChdgG (B:s
(3Ydi GHf ZdHhf heY GdJhSW aj Ch JObjb SNQ hGejf s
(3BNQgG (B:s
(3heY GdgGA hbaG dCHj GdcQe Yf jYbhH hjeJfY gGA GdScJ aj GdYGdejf HChd GdShQI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B54 - (3U(B218s
(3GdfSNI HgG MhGTs
(3hYeOI GdYQaGf QGFjI cGdefXheI GdLRQjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1168s
Keywords: (3GdbQGAGJ hGdJLhjOs